La formazione musicale storico-culturale nell’infanzia - Carla Cuomo; Nicola Badolato (Musica Docta)
Models of musical education in childhood are linked to the idea of ‘childhood’ itself, to the sensibility that underpins it, and thus to the idea of school and education that adheres to it. This paper examines the idea of childhood and the educational goals of school as expressed in various documents, both from the EU and from Italy. These documents emphasise the notion of ‘quality’ in school education, and the need to build European citizenship from early childhood. In the light of these documents, the paper is divided into two parts. The first explains why one of the pillars of historical and cultural music education in childhood (0-10 years) should be artistic music education, and how the latter can be developed for the purpose of building historical thinking. The second part establishes a link between this specific training and the didactics of listening, looking in particular at the possibility of combining the study and analysis of the formal and narrative musical structures in a piece of art music with the improvement of the perception of the ‘before-now-after’ timeline, a concept that underlies the work of teachers in the historical-anthropological field, especially in primary schools.